Clinical dividends from the molecular genetic diagnosis of craniosynostosis. - Wilkie, A; Bochukova, E; Hansen, R; Taylor, I; Rannan-Eliya, S; Byren, J; Wall, SA; Ramos, L; Venâncio, M; Hurst, J; O'rourke, A; Williams, L; et al. (2007)
A dozen years have passed since the first genetic lesion was identified in a family with craniosynostosis, the premature fusion of the cranial sutures. Subsequently, mutations in the FGFR2, FGFR3, TWIST1, and EFNB1 genes have been shown to account for approximately 25% of craniosynostosis, whilst several additional genes make minor contributions. Using specific examples, we show how these discoveries have enabled refinement of information on diagnosis, recurrence risk, prognosis for mental development, and surgical planning. However, phenotypic variability can present a significant challenge to the clinical interpretation of molecular genetic tests. In particular, the difficulty of analyzing the complex interaction of genetic background and prenatal environment in determining clinical features, limits the value of identifying low penetrance mutations.